TINJAUAN YURIDIS PERANAN ADVOKAT DALAM PENYELESAIAN SENGKETA YANG DITENTUKAN OLEH KLIEN - Manullang, Rusmini Luciani; Besty Habeahan (Judge : Jurnal Hukum, 2026)
Dispute resolution in Indonesia has evolved from a traditional, customary-based mechanism to a modern legal system that positions advocates as key actors in the law enforcement process. The issues addressed in this study are analyzing the role of advocates in client-determined dispute resolution and assessing the extent to which advocate assistance can influence the final outcome of a dispute. Using a normative and empirical juridical approach through interviews with practicing advocates, this study found that advocates play a strategic role as legal advisors, legal representatives, protectors of client rights, designers of dispute resolution strategies, and guardians of the ethics and integrity of the legal process. However, advocates cannot guarantee victory in a case because the decision remains in the hands of the judge, arbitrator, or mediator and is heavily influenced by the strength of the available legal evidence and facts. Advocate assistance primarily serves to increase the client's chances of success through appropriate legal strategies, risk management, and effective evidence, rather than guaranteeing results. The findings of this study emphasize the importance of two-way communication, honesty of client information, and advocate professionalism in maintaining the quality of the dispute resolution process. This research contributes to a stronger understanding of the dynamics of the advocate-client relationship and its implications for the effectiveness of the dispute resolution system in Indonesia.